(untitled) (Південний архів (історичні науки), 2022)
Purpose. In the article, the authors, based on the analysis of a number of historiographical sources, describe the pre- Easter customs and rites, their structural elements and reveal the main traditions of celebrating the holidays of Lent, Lent, Annunciation and Palm Sunday. The economic rituals of the Lemkos, which are closely connected with the spring field work, are highlighted. It has been found that in the past they were an integral part of the first plowing and grazing process. It was found that the labor rituals of the population of Lemkivshchyna at the national level are determined by certain features and variations. The local peculiarities of the research rituals of the population of Lemkivshchyna are revealed and the place of this system of rituals in the array of all-Ukrainian traditions is outlined through the prism of their economic motives. Methods. The solution of this goal is realized through historical methods (comparative-historical, problemchronological, comparative-ethnographic). Results. Scientific novelty lies in a thorough analysis of the whole complex of rites and customs of the pre-Easter cycle of Lemko holidays and their place in the ethnocultural space of Ukrainians. The meanings of the influence of research rituals on modern society are revealed. Conclusions. The study of the traditions of celebrating the pre-Easter holidays of the population of Lemko region allows modern generations to solve a number of problems today: preservation of ancestral memory, study of the origins of ethnic group spirituality in local diversity, humanization of culture for prospects. Discovering the place and role of the pre-Easter cycle of holidays in the spiritual process of the present and attempts to predict its functioning in the future.